Hurry home : a novel - Nay, Roz (Crooked Lane, 2020)
"From the bestselling author of Our Little Secret comes a suspenseful new thriller featuring two estranged sisters desperate to keep their deepest and darkest secret where it belongs--in the past. Blood is thicker than water... And it could cost you everything. Alexandra Van Ness has the perfect life. She lives in an idyllic resort town tucked away in the Rocky Mountains, shares a designer loft with her handsome boyfriend, Chase, and has her dream job working in child protection. Every day, Alex goes above and beyond to save children at risk. But when her long-lost sister, Ruth, unexpectedly shows up at her door, Alex's perfect life is upended. Growing up, Ruth was always the troublemaker, pulling Alex into her messes, and this time will be no different. Still, Alex will help Ruth under one condition: we will never, ever, talk about the past. But when a local child goes missing, both women are forced to confront the secrets they've promised to keep buried. Utterly engrossing and claustrophobic, Hurry Home is a tantalizing reflection of the chain-and-shackles relationship between sisters that asks: what lines wouldn't you cross for your own?"--Jacket flap.